Market and other factors affecting farm specific production efficiency in pig production in Vietnam - Jabbar, M.A.; Akter, S. (Informa UK Limited, 2008)
In developing country production environment, farm production efficiency is often measured in terms of on-farm resources and producer characteristics. In this paper we postulate that input and output market related factors also influence farm production decisions hence its efficiency. Stochastic frontier production function was used to assess technical efficiency and its determinants including input and output market variables for a sample of 1962 pig farms in Vietnam with data collected in 1999. There are significant differences in production behavior and efficiency level between the North and the South, among farms producing different breeds, between mixed and specialized farms, between household and commercial farms, and among producers located in different agro-ecological regions. Access to better output market, land size, herd size, and education of household head significantly reduced inefficiency, while access to government supplied inputs, age of household head, female headed households and family supplied crude feeds significantly increased inefficiency in both the regions. The direction of influence on efficiency differs between the two regions for access to credit, proportion of output sold at market rather than at farm gate and family labor supply. Generally, market related factors had more consistent influence on production efficiency in the South of Vietnam where the experience of market economics is longer compared to the North. Policy actions on providing better extension, more timely access to better quality inputs through the private sector, making credit more easily accessible to smallholders and opportunity to sell output at better priced secondary markets are expected to increase productivity and reduce inefficiency.